2001
DOI: 10.1126/science.1060949
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Gene Associated with Bt Resistance in Heliothis virescens

Abstract: Transgenic crops producing insecticidal toxins from Bacillus thuringiensis (Bt) are widely used for pest control. Bt-resistant insect strains have been studied, but the molecular basis of resistance has remained elusive. Here, we show that disruption of a cadherin-superfamily gene by retrotransposon-mediated insertion was linked to high levels of resistance to the Bt toxin Cry1Ac in the cotton pest Heliothis virescens. Monitoring the early phases of Bt resistance evolution in the field has been viewed as cruci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
499
3
6

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 557 publications
(517 citation statements)
references
References 15 publications
9
499
3
6
Order By: Relevance
“…31,50 BT-R 1 homologs are the principal determinant for Cry1A toxin action in lepidopteran insects. [30][31][32][33][34][35] No BT-R 1 homologs has been identified in vertebrates, suggesting that these particular cadherin receptors represent a unique family of proteins in invertebrates, particularly insects, and may explain why Cry toxins are not toxic to mammalian cells. Perhaps, Cry toxins once constituted virulence factors with the ability to destroy cells through oligomerization and incorporation of toxin molecules into cell membranes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31,50 BT-R 1 homologs are the principal determinant for Cry1A toxin action in lepidopteran insects. [30][31][32][33][34][35] No BT-R 1 homologs has been identified in vertebrates, suggesting that these particular cadherin receptors represent a unique family of proteins in invertebrates, particularly insects, and may explain why Cry toxins are not toxic to mammalian cells. Perhaps, Cry toxins once constituted virulence factors with the ability to destroy cells through oligomerization and incorporation of toxin molecules into cell membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Cry toxins bind to their respective cadherin receptors with high affinity and specificity, the disruption or absence of which results in loss of susceptibility to Cry toxin. [33][34][35] So far, the role of BT-R 1 in the cytotoxic action of Cry toxin has not been defined.…”
Section: Introductionmentioning
confidence: 99%
“…A Manduca sexta 210-kDa E-cadherin-like peptide bound activated (trypsinized) Cry1A toxin (Francis and Bulla, 1997). Midgut expressed cadherinlike cDNAs were isolated from M. sexta (Vadlamudi et al, 1995), Bombyx mori (Nagamatsu et al, 1998a), Heliothis virescens (Gahan et al, 2001), and Pectinophora gossypiella (Morin et al, 2003). Furthermore, a cadherin knockout from a transposon insertion resulted in 40,000-fold resistance in the H. virescens YHD2 colony (Gahan et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Midgut expressed cadherinlike cDNAs were isolated from M. sexta (Vadlamudi et al, 1995), Bombyx mori (Nagamatsu et al, 1998a), Heliothis virescens (Gahan et al, 2001), and Pectinophora gossypiella (Morin et al, 2003). Furthermore, a cadherin knockout from a transposon insertion resulted in 40,000-fold resistance in the H. virescens YHD2 colony (Gahan et al, 2001). Segregation of alleles at a cadherin locus was associated with resistance in P. gossypiella strain AZP-R (Morin et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Also, specific differences in the biochemical pathways of the pheromone components between Hv and Hs are currently being unraveled (Choi et al, 2004), which can lead to the identification of candidate genes. Earlier we have demonstrated that it was possible to use a combination of mapping and candidate genes to identify and sequence one important gene in Hv (Gahan et al, 2001). With the identification of genes underlying pheromonal differences between the species, the sequences of these genes in different geographic populations can be examined to determine patterns of synonymous and non-synonymous substitutions within and between species, indicating the action of selection (e.g., Taylor et al, 1996;Tsaur et al, 1998).…”
Section: Discussionmentioning
confidence: 99%